Education Quality and Performance Based on Balanced Scorecard in Junior High School : A Case Study at SMPN 8 Insumbrei Supiori Regency, Papua - Yulianingsih, Yulianingsih; Ismanto, Bambang; Wasitohadi, Wasitohadi (Universitas Pendidikan Mandalika, 2024)
This research aims to analyze the performance and quality of education based on the four perspectives of the balanced Scorecard at Junior high school (SMPN) 8 Insumbrei, Supiori Regency, Papua. The research used a qualitative approach with a case study method utilizing the Balanced Scorecard perspectives, including the financial, customer, internal business, and growth and learning perspectives. The research subjects included 27 individuals, consisting of 9 teachers, 10 students, and 8 community members. Data collection techniques involved documentation analysis, questionnaires, and interviews. Data analysis followed the Miles and Huberman model, encompassing interactive data analysis involving data collection, reduction, display, and conclusion drawing. The research findings showed that: 1) from a financial perspective, in economic terms, effectiveness and efficiency score 4 with a good category, 2) from a customer perspective, it scores 4 with a good category, 3) based on the internal business perspective, the measurement results show a score of 3 with enough category, and 4) from a learning and growth perspective, it scores 4 with a good category.